The Atlantic Crossing - Maddocks, Melvin; Editors of Time-Life Books (Amsterdam Time-Life Books, 1981)
A comic science-fiction novel by the film director Ken Russell. In the beginning was a spaceship, and both of its crew members were robots. They are all set to consign two experimental human prototypes, named Adam and Eve after a couple of pot-plants, to the surface of a planet called Earth.
Includes Index and Colored Illutstraiotns
Keywords: Navigation